2019
DOI: 10.1149/2.1221910jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Raman Spectroscopic Investigations on the Speciation and Behavior of Chromium Ions in Fluoride Doped Molten LiCl-KCl

Abstract: The speciation and behavior of chromium ions in LiCl-KCl-CrF 3 and LiCl-KCl-LiF-CrF 3 melts were investigated by using cyclic voltammetry, square wave voltammetry, chronopotentiometry and Raman spectroscopy. Electrochemical reduction of Cr(III) to Cr(0) in LiCl-KCl-CrF 3 is a two-step process mediated by the formation of Cr(II). Most Cr(III) ions exist in the form of CrCl 6 3− while CrCl 6-x F x 3− (x ≤ 3) ions are minor in the molten salt medium. Based on the cyclic voltammetric results obtained at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…It is well-known that group 3 fluorometallates such as ScF 6 3– can be readily synthesized via the reaction of corresponding metal fluorides in excess HF and NH 4 F solutions, and the coordination structures of solid-state fluorometallates are therefore well characterized using a series of spectroscopic methods. , In addition to the aqueous medium, molten fluoride such as FLiNaK is also a kind of appropriate medium that can be employed for the synthesis of group 3 fluorometallates due to the presence of free F – anions. , By varying the ratio of MF 3 and FLiNaK, it is possible to probe the coordination structures of binary fluorometallates that are not isolable in solid state, which not only provide a unique opportunity for a comprehensive understanding of the coordination chemistry of group 3 metal fluorides but also help solve the technical problems such as those involved in the manufacture of aluminum–scandium master alloy, , which is related to the speciation of metal fluoride in a molten salt environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that group 3 fluorometallates such as ScF 6 3– can be readily synthesized via the reaction of corresponding metal fluorides in excess HF and NH 4 F solutions, and the coordination structures of solid-state fluorometallates are therefore well characterized using a series of spectroscopic methods. , In addition to the aqueous medium, molten fluoride such as FLiNaK is also a kind of appropriate medium that can be employed for the synthesis of group 3 fluorometallates due to the presence of free F – anions. , By varying the ratio of MF 3 and FLiNaK, it is possible to probe the coordination structures of binary fluorometallates that are not isolable in solid state, which not only provide a unique opportunity for a comprehensive understanding of the coordination chemistry of group 3 metal fluorides but also help solve the technical problems such as those involved in the manufacture of aluminum–scandium master alloy, , which is related to the speciation of metal fluoride in a molten salt environment.…”
Section: Introductionmentioning
confidence: 99%
“…species is expected in accordance with the low polarizing power of these trivalent cations. Although this deduction is supported by some electrochemical studies, additional work on the solution structure of molten salts is needed for further verification [5d,22] …”
Section: Resultsmentioning
confidence: 97%
“…Our recent study on the LiCl-KCl-CrF 3 melt revealed that the presence of fluoride ions could cause the appearance of additional feature in the voltammagram due to the formation of metal complexes with mixed fluoride and chloride ions. 31 It is therefore necessary to explore whether the same effect works in the LiCl-KCl-ThF 4 case that could cause the appearance of peak R 2 and its unusual number of exchanged electrons. 4 shows a series of square wave voltammagrams of molten LiCl-KCl-ThF 4 with different concentrations of fluoride ions adjusted by LiF addition.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to what was observed when excess LiF was added into the LiCl-KCl-CrF 3 melt, during which CrCl 6 3− was converted to CrCl 6−x F x 3− . 31 As a result, it is possible that the R 2 peak also arises from reduction of Th(IV) to Th(0), but Th(IV) is actually in the form of ThCl x F y z− when the LiF/ThF 4 molar ratio was varied.…”
Section: Resultsmentioning
confidence: 99%